Interaction effects between entomopathogenic fungi and neonicotinoid insecticides against Lipaphis erysimi in vegetable ecosystem - HALDER, JAYDEEP; KUSHWAHA, DEEPAK; RAI, A B; SINGH, B (The Indian Journal of Agricultural Sciences, 2019)
Efficacy of different entomopathogenic fungi (EPF), viz. Beauveria bassiana, Metarhizium anisopliae and Lecanicillium (=Verticillium) lecanii and neonicotinoid insecticides (Imidacloprid and Thiamethoxam) were evaluated alone and their 1:1 combination against Lipaphis erysimi prevalent in vegetable ecosystem. Among the entomopathogenic fungi, L. lecanii was found most promising, registering lowest median lethal time (LT50) of 41.46 h, 44.09 h and 44.83 h during the period of 2015, 2016 and 2017, respectively; followed by B. bassiana (44.07 h, 53.22 h and 51.60 h) and M. anisopliae (46.86 h, 48.83 h and 48.99 h). Amongst the two neonicotinoids, Thiamethoxam was found more efficacious than the Imidacloprid. Blending of L. lecanii and Thiamethoxam at half of their recommended dose took lowest (13.39 h, 15.66 h and 17.41 h during 2015, 2016 and 2017, respectively) lethal time to kill the 50% test population followed by B. bassiana + Thiamethoxam (15.86 h, 17.72 h, 20.86 h) and M. anisopliae + Thiamethoxam (18.28 h, 19.69 h, 21.86 h). Combinations of these entomopathogenic fungi and neonicotinoid insecticides had co-toxicity co-efficient values >1 and lower LT50 values than each of their individual indicating the compatibility amongst them. Co-application of these EPF with sub-lethal concentration of neonicotinoids could not only be a green ecofriendly option against this sucking pest but also able to minimize the chemical insecticides load in the environment.